The Myth of the Marcoses a discourse-mythological analysis of SMNI news' coverage of Marcos Jr.'s 2022 presidential campaign. - Calumbiran, Arianne Jeanel F.
This thesis investigates whether Pastor Apollo Quiboloy’s Sonshine Media Network Inc. (SMNI), through its news coverage of Ferdinand “Bongbong” Marcos Jr.’s presidential campaign, contributed to the creation of a mythology of the Marcos family, under the assumption that the network worked to help catapult them back to Malacañang based on the public endorsement given by the Pastor for Marcos Jr.’s candidacy, and the Center for Media Freedom and Responsibility’s (2022) flagging of the network’s “extreme partisanship” during the elections. By using Kelsey (2015)’s Discourse Mythological Approach to Critical Discourse Analysis, this research examines the text, discursive practices, and social practices involved in SMNI’s production of news stories that may have contributed to the overall construction of a mythicized view of the Marcos family. Marcos Jr.’s campaign is of significance as his aimed election signified the political family’s return to the country’s helm decades after being overthrown by the Filipinos due to horrors under Ferdinand Marcos Sr.’s regime. Results of the qualitative analysis suggest the mythologizing of Marcos Jr. as a hero reborn from two key fallen heroes in the narrative, Marcos Sr., and Rodrigo Duterte. SMNI News’ narrative also suggests the mythologizing of Quiboloy as a prophet.